The Effect of Using E-modules in Biology Learning on Learning Outcomes of High School and University Students: Meta-Analysis - Arifin, Nurfadila; Effendi, M. Harja; Purwati, Nining (Universitas Islam Negeri Mataram, 2024)
This study aims to determine the effect size (ES) of the application of e-modules in biology learning on student's learning outcomes. This study uses the type of meta-analysis research. The research sample consisted of 14 articles sourced from the results of article identification through Google Scholar and Eric. The research data were collected based on the reference of inclusion and exclusion criteria. Data analysis was conducted by calculating the ES value using Cohen’s d formula. The results of data analysis showed that there were 14 articles divided into two levels of education, namely high school (9 articles) and university (5 articles) with a total average effect size score of 1,14 which means the effect size criteria are very large (VL). The ES average score for the high school level is 1,20 or very large (VL) ES average, while the ES average score for the university level is 1,02 or categorized as large (L) ES average. Therefore, it can be concluded that the effect size of the application of e-modules in biology learning has a significant impact on improving student learning outcomes.